Post activation potentiation for lower limb with eccentric and concentric movements on sprinters - Dechechi, C.; Lopes, C.; Galatti, L. R.; Ribeiro, R. (International Journal of Sports Science, 2013)
Muscle contractions preceding to high intensity activity can result in increased force and power generation (postactivation potentiation[PAP]). Although the type of muscular contractions could affect subsequent strength and power performance, little information exists on their effects. According to some authors augmentation is one of the most frequently used methods to acquire the strength and rapid reaction capacity of the muscle immediately. In this work was evaluated the effects of post-activation potentiation (PAP) for lower limb movements with eccentric and concentric sprinters . The study included 10 males with 15.8 ± 0.8 years, 67 ± 7.41 kg bw and 1.75 ± 0.07 m in height. The test had 05 sessions with a minimum interval of 72 hours between each session, with the first 3 familiarization sessions and testing of 1RM concentric and eccentric, then the collections have more tests in two sessions with one another in the concentric phase and the eccentric with 50m shot. The results presented here underscore the importance of training loads in concentric actions, because the speeds achieved are higher than those of the eccentric actions, showing significant gains in strength after the PPA of the concentric squat.